A Comparative Study of Cloud based ERP systems with Traditional ERP and Analysis of Cloud ERP implementation (International Journal of Engineering and Computer Science, 2018)
Cloud based ERP system architecture provides solutions to all the difficulties encountered by conventional ERP systems. It provides flexibility to the existing ERP systems and improves overall efficiency. This paper aimed at comparing the performance traditional ERP systems with cloud base ERP architectures. The challenges before the conventional ERP implementations are analyzed. All the main aspects of an ERP systems are compared with cloud based approach. The distinct advantages of cloud ERP are explained. The difficulties in cloud architecture are also mentioned.